Factors Influencing the Needs to Develop the Potential of Personnel in Local Administrative Organizations in Udon Thani Province - Sittivongsa, Boonpeng (City State Journal, 2024)
This research article aims to study (1) the needs for developing the potential of personnel in the local administrative organization in Udon Thani province, (2) factors influencing the Needs to develop the potential of personnel in local administrative organizations in Udon Thani province, and study (3) guidelines for the needs of developing the potential of personnel in local administrative organizations in Udon Thani province. This research used both quantitative and qualitative research methods. The samples used in the research were 394 personnel in local administrative organizations in Udon Thani province and 10 key informants. The research instruments used were questionnaires and interviews. The statistics used in data analysis were frequency, percentage, mean, standard deviation, and multiple regression analysis using a hierarchical variable selection method. Findings are as follows: (1) The needs for developing the potential of personnel in the local administrative organization in Udon Thani province. Overall, it was at a moderate level ( = 3.02, SD = 0.16). Considering each item in descending order as follows, it was found that ethics ( = 3.34, SD = 0.75), vision ( = 3.29, SD = 0.45), Morality ( = 3.04, SD = 0.54) respectively. (2) Factors influencing the needs to develop the potential of personnel in local administrative organizations in Udon Thani province statistically significant at the .05 level include support from management (X5), motivation (X4), participation (X1). The coefficient of the predictor in the raw score (b) is equal to .348, .302 and –.060 respectively. (3) Personnel should be developed to have vision in the organization, build human relations in the organization with personnel, and always give advice on work regarding duties including providing assistance to colleagues in solving various problems according to the spirit and vision of local agencies. Seriously develop and promote morality for personnel in local agencies and develop personnel to have ethics in performing their duties at work in a concrete way and create awareness of the effective application of ethics in the organization.